Esplorare il territorio Linee di ricerca socio-spaziali - BERGAMASCHI, MAURIZIO; LOMONACO, ALICE (Sociologia del territorio, 2022)
This volume was developed within the framework of the teaching course of Urban Sociology in which seminar activities had been planned to respond to a significant teaching demand: to show students the polyhedral nature of studies and research located within the discipline. At the same time, it was intended to highlight the common heuristic option, going beyond the first impression of a magmatic accumulation of research strands. By involving young researchers, the seminar activity thus was designed not to focus on a specific research topic to be explored in depth during the various scheduled classes but to draw attention to the explanatory value of the territorial dimension in understanding a multiplicity of social phenomena, even where this was not immediately evident and often not adequately recognized. The researches outlined in the volume have the merit of focusing on spatial and territorial aspects of the different social forms studied, contributing to the spatialization of sociological theory. In this reading, the territory emerges not just as a mere background and container for a set of social processes but a dimension socially structured by the forces in play and, at the same time, structuring them.